1
$\begingroup$

I've been stuck on this problem over the weekend so I decided to ask for some direction. The problem reads:

"The multiplication theorem for series requires that the two series be absolutely convergent; if this condition is not met, their product may be divergent. Show that the series $\sum_{0}^{\infty}\frac{(-1)^i}{\sqrt{i + 1}}$ gives an example: it is conditionally convergent, but its product with itself is divergent. Estimate the size of the odd terms $c_{2n+1} $ in the product."

I shall refer to $\frac{(-1)^i}{\sqrt{i + 1}}$ as $a_n$. I would imagine this converges because it's an alternating sum. I was thinking of rearranging the terms of the series so that I have all $\sum a_n$= $\sum (a_{n}^{+} - a_{n}^{-})$. However, this is where I am stuck. I am not sure where to take it from there. I was thinking of breaking up the sum into two different series such that $\sum (-1)^i$ and $\sum \frac{1}{\sqrt{i + 1}}$, the first sum would be -1 + 1 + -1 + 1 +.... Depending on how you rearrange this one, it could be -1, 0, or 1 I think.

I think the $\sum \frac{1}{\sqrt{i + 1}}$ diverges. I know the sum of $\frac{1}{n}$ does diverge. I was relating it to that.

However, I fear I am over thinking the whole problem. I need help.

Thanks you for taking the time to read this post and thanks in advanced to those who comment.

$\endgroup$
  • $\begingroup$ they told you it is conditionally convergent already. All you have to do is actually write the Cauchy product and show it diverges. $\endgroup$ – oldrinb Oct 8 '13 at 4:24
  • $\begingroup$ So I was over thinking it then. $\endgroup$ – Kevin_H Oct 8 '13 at 19:39
0
$\begingroup$

The series $$ \sum_{k=0}^\infty\frac{(-1)^k}{\sqrt {k+1}} $$ is convergent by the Leibnitz criterion, because it is alternating and the general term goes to zero. It is not absolutely convergent because $$ \sum_{k=0}^\infty\frac{1}{\sqrt {k+1}}\geq\sum_{k=1}^\infty\frac1{k+1}=+\infty. $$ Finally, $$ \sum_{k=0}^\infty\frac{(-1)^k}{\sqrt {k+1}}\,\cdot\,\sum_{k=0}^\infty\frac{(-1)^k}{\sqrt {k+1}}=\sum_{n=0}^\infty\left(\sum_{k=0}^n\frac{(-1)^k}{\sqrt {k+1}}\,\frac{(-1)^{n-k}}{\sqrt{n+1- k}}\right)\\=\sum_{n=1}^\infty\,(-1)^n\sum_{k=0}^n\frac1{\sqrt{(k+1)(n+1-k)}} $$ Now note that the expression $(k+1)(n+1-k)$ is a downwards parabola on $k$, and so it has a maximum. Elementary calculus shows this maximum to occurs at $k=n/2$, so $$ (k+1)(n+1-k)\leq(n/2+1)(n/2+1)=(n+1)^2/4. $$ So $$ \sum_{k=0}^n\frac1{\sqrt{(k+1)(n+1-k)}}\geq\sum_{k=0}^n\frac2{\sqrt{(n+1)^2}}=\sum_{k=0}^n\frac2{n+1}=2. $$ The general term does not go to zero, and so the product series is divergent.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.